An overview of bioaerosol load and health impacts associated with dust storms: A focus on the Middle East. (15th February 2020) - Soleimani, Zahra; Teymouri, Pari; Darvishi Boloorani, Ali; Mesdaghinia, Alireza; Middleton, Nick; Griffin, Dale W.
Abstract: Dust storms are an important environmental problem worldwide. The main sources of dust storms include the Sahara, the Middle East, and central and northeastern Asia. Dust originating from these regions can be dispersed across oceans and in some cases globally. The storms occur throughout the year and vary in frequency and intensity. The biological agents (e.g., fungi, bacteria and viruses) and the mineral and chemical compositions of dust may have adverse effects on human health and quality of life. Desert dusts may cause respiratory diseases, cardiovascular diseases, cardiopulmonary diseases, mental health issues, injuries and death from transport accidents caused by poor visibility. This paper presents dust storm human health research conducted in the Middle East in both indoor and outdoor environments. Results illustrate that particle concentration and bioaerosol types in the atmosphere are affected by climate change and meteorological factors. Recent data trends indicate that annual dust aerosol concentrations have increased worldwide. According to studies conducted in the Middle East, the incidence of respiratory and cardiovascular mortality and hospital visits have increased dramatically following dust storm exposures but very few have demonstrated a regional causation. National and international collaborative research is needed to advance our understanding of the global implications of dust storms and what may be the most effective means of mitigation. Highlights: First review study of its kind to present on dust storms and their impact health and bioaerosols in the Middle East. The Middle East has heavy PM10 loads that are due to dust storms. A review of dust event studies, their particulate matter concentrations, their points of origins, seasonality and movement routes have been summarized in this paper. Aerobiology: collection, concentration and identification of microorganisms. The influence of environmental factors on the viability of microorganisms in the atmosphere and the health effects of bioaerosol (bacteria, fungi) exposure.